MANAJEMEN EKONOMI MANDIRI DALAM KEMANDIRIAN PESANTREN UPAYA MENINGKATKAN KETAHANAN EKONOMI MASYARAKAT - Roiqotul Fitria; Shevina Nazalia Rachamadinim; Siti Rohma (IZZI: Jurnal Ekonomi Islam, 2024)
This study aims to describe the application of independent economic management in Pondok Pesantren Al-Mashduqiah as an effort to improve the economic resilience of the surrounding community. By using qualitative descriptive method, this study identifies pesantren business units, such as savings and loans, convection, tofu and tempeh factory, wholesale, and cooperative, which become the main source of income. The findings show that such efforts help pesantren meet internal needs and support economic resilience. However, the contribution to the surrounding community is still limited. This study highlights the importance of training, external support, and the use of technology as a strategy for developing a more inclusive pesantren economy.